Genome-Wide Copy Number Variation Scan Identifies Complement Component C4 as Novel Susceptibility Gene for Crohn's Disease. Issue 3 (March 2016) - Cleynen, Isabelle; Konings, Peter; Robberecht, Caroline; Laukens, Debby; Amininejad, Leila; Théâtre, Emilie; Machiels, Kathleen; Arijs, Ingrid; Rutgeerts, Paul; Louis, Edouard; Franchimont, Denis; De Vos, Martine; et al.
Abstract : Background: The genetic component of Crohn's disease (CD) is well known, with 140 susceptibility loci identified so far. In addition to single nucleotide polymorphisms typically studied in genome-wide scans, copy number variation is responsible for a large proportion of human genetic variation. Methods: We performed a genome-wide search for copy number variants associated with CD using array comparative genomic hybridization. One of the found regions was validated independently through real-time PCR. Serum levels of the found gene were measured in patients and control subjects. Results: We found copy number differences for the C4S and C4L gene variants of complement component C4 in the central major histocompatibility complex region on chromosome 6p21. Specifically, we saw that CD patients tend to have lower C4L and higher C4S copies than control subjects ( P = 5.00 × 10 −03 and P = 9.11 × 10 −04 ), which was independent of known associated classical HLA I and II alleles ( P = 7.68 × 10 −03 and P = 6.29 × 10 −03 ). Although C4 serum levels were not different between patients and control subjects, the relationship between C4 copy number and serum level was different for patients and control subjects with higher copy numbers leading to higher serum concentrations in control subjects, compared with CD patients ( P < 0.001). Conclusions: C4 is part of the classical activation pathway of the complement system, which is important for (auto)immunity. Low C4L or high C4S copy number, and corresponding effects on C4 serum level, could lead to an exaggerated response against infections, possibly leading to (auto)immune disease. Abstract : Article first published online 23 November 2015.Supplemental Digital Content is Available in the Text.